Sialadenoma Papilliferum of the Bronchus: An Unrecognized Bronchial Counterpart of the Salivary Gland Tumor With Frequent BRAF V600E Mutations. (May 2021) - Nakaguro, Masato; Mino-Kenudson, Mari; Urano, Makoto; Ogawa, Ikuko; Honda, Yumi; Hirai, Hideaki; Tanigawa, Maki; Sukeda, Aoi; Kajiwara, Naohiro; Ohira, Tatsuo; Ikeda, Norihiko; Mikami, Yoshiki; et al.
Abstract : Sialadenoma papilliferum (SP) is a rare benign tumor of the salivary glands, and only 3 unequivocal cases of SP arising in the bronchus have been reported. We herein describe the histomorphologic and molecular features of 4 bronchial SP cases and discuss the differential diagnosis of this entity and the relationship with its clinicopathologic mimics, in particular, glandular papilloma and mixed squamous cell and glandular papilloma (GP/MP). We encountered 2 male and 2 female patients with bronchial SP (mean: 66.8 y old). All 4 tumors arose in the central bronchus and were characterized by a combination of surface exophytic endobronchial papillary proliferation and a submucosal multicystic component with complex architecture. The neoplastic epithelium consisted predominantly of nonciliated stratified columnar cells with ciliated, squamous, and mucinous cells present focally. While 2 tumors (50%) harbored a BRAF V600E mutation by molecular and immunohistochemical analysis, similar to GP/MP, no KRAS, HRAS, AKT1, or PIK3CA mutations were detected in any of the cases. Two patients were treated with limited resection, while 2 patients underwent lobectomy based on the diagnosis of adenocarcinoma or possible squamous cell carcinoma in situ in the preoperative biopsy. All survived without recurrence or metastasis for 23 to 122 months after treatment. SP can develop in the central bronchus as the bronchial counterpart of the salivary gland tumor and should be considered in the differential diagnosis of endobronchial tumors. In addition, some histologic resemblance and frequent BRAF V600E mutation raise the possibility of SP and GP/MP being on the same disease spectrum. Abstract : Supplemental Digital Content is available in the text.